Переваги та недоліки лібералізації валютного регулювання в Україні - Кузнєцова, Анжела; Місяць, Наталія; Kuznetsova, Anzhela; Misiats, Nataliia (ТНЕУ, 2017)
Висвітлено основні переваги та недоліки лібералізації валютного регулювання, а також особливості цього процесу для країн, що розвиваються. Визначено комплекс факторів, які суттєво знижують ефективність лібералізації в Україні, у зв’язку з чим акцентовано увагу на необхідності створення передумов для можливості досягнення позитивних результатів лібералізації. Запропоновано послідовність заходів із лібералізації валютного регулювання, яка містить, зокрема, визначення рівня ризику валютних операцій щодо їх проведення з метою непродуктивного виведення капіталу за межі України. Introduction. The high openness level of the Ukrainian economy determines the necessity of join to the worldwide financial integration by means of gradual liberalization as a part of the foreign currency exchange arrangements reform. Purpose. The main aim of the paper is to develop methodological and applied principles for the foreign currency exchange liberalization in Ukraine. Results. It has been summarized the liberalization advantages and disadvantages, identified current economic items which prevent to achieve the liberalization positive consequences in Ukraine, defined the favorable sequence of the liberalization steps in Ukraine which also contains measures of recognizing foreign currency exchange transactions aimed for capital outflow. For successful liberalization it is necessary to enroot a precondition complex which is consists of economic, monetary, financial and institutional reforms. Conclusion. Tht main goals of the liberalization in Ukraine are the next: to attract the long-term capital inflows from developed economies, to obtain access to the global financial markets, to take liberalization advantages and to reduce its disadvantages and risks.
Advantages and disadvantages of the liberalization of foreign currency exchange arrangements in Ukraine
Keywords: валютне регулювання; лібералізація; транскордонний рух потоків капіталу; передумови лібералізації; наслідки лібералізації; послідовність заходів із лібералізації; foreign currency exchange arrangements; liberalization; capital inflows and outflows; liberalization preconditions; liberalization consequences; sequence of liberalization measures